2015
DOI: 10.1021/acs.jmedchem.5b00698
|View full text |Cite
|
Sign up to set email alerts
|

Selexipag: An Oral and Selective IP Prostacyclin Receptor Agonist for the Treatment of Pulmonary Arterial Hypertension

Abstract: Prostacyclin controls cardiovascular function via activation of the prostacyclin receptor. Decreased prostacyclin production occurs in several cardiovascular diseases. However, the clinical use of prostacyclin and its analogues is complicated by their chemical and metabolic instability. A medicinal chemistry program searched for novel nonprostanoid prostacyclin receptor agonists not subject to these limitations. A compound with a diphenylpyrazine structural core was synthesized. Metabolic stability and agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…More importantly, beraprost and iloprost also bind to other prostanoid receptors especially the EP 3 receptor 7, 8 , potentially causing unsafe side effects such as marked hypotension, increased heart rate, impaired gastrointestinal function, and lung arterial contraction 7, 27, 28 , which limits their clinical use. As a highly specific and clinically available IP receptor agonist used in the treatment of pulmonary hypertension 9, 10 , our data for the first time demonstrated that delayed treatment with MRE-269 reduced infarct volume in aged rats subjected to transient MCAO, suggesting a potentially valuable application in the treatment of ischemic stroke.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…More importantly, beraprost and iloprost also bind to other prostanoid receptors especially the EP 3 receptor 7, 8 , potentially causing unsafe side effects such as marked hypotension, increased heart rate, impaired gastrointestinal function, and lung arterial contraction 7, 27, 28 , which limits their clinical use. As a highly specific and clinically available IP receptor agonist used in the treatment of pulmonary hypertension 9, 10 , our data for the first time demonstrated that delayed treatment with MRE-269 reduced infarct volume in aged rats subjected to transient MCAO, suggesting a potentially valuable application in the treatment of ischemic stroke.…”
Section: Discussionmentioning
confidence: 74%
“…Pharmacokinetics in rats, dogs, and humans showed a significantly improved t½ of 6–8h 7, 8 . After successful clinical trials 9, 10 , selexipag/MRE-269 has FDA approval for pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…11 An active metabolite of selexipag, MRE-269, shows high selectivity to the IP receptor, and its long half-life enables a twice-a-day oral dosing regiment. 12 Thirty-nine countries jointly participated in a doubleblind, placebo-controlled Phase III study with selexipag, with 1,156 PAH patients (GRIPHON study). 13 The primary endpoint was a composite of death from any cause or a complication related to PAH up to the end of the treatment period.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…To overcome the aforementioned pharmacologic limitations associated with PGI 2 structures, Actelion/Nippon Shinyaku have developed a selective, oral nonprostanoid IP receptor agonist, selexipag (2-{4-[(5,6-diphenylpyrazin-2-yl)(isopropyl) amino]butoxy}-N-(methylsulfonyl)acetamide, previously known as NS-304) (Asaki et al, 2015), which has been recently approved in the United States, the European Union, and Japan for the treatment of PAH (Sitbon et al, 2015). After systemic absorption, selexipag, the parent drug, is hydrolyzed to the highly potent metabolite ACT-333679 ({4-[(5,6-diphenylpyrazin-2-yl)(isopropyl)amino]butoxy}acetic acid, previously known as MRE-269), the major driver of clinical efficacy ( Fig.…”
Section: Introductionmentioning
confidence: 99%